See You in Court! How to Avoid IDEA Transition–Related Mediations and Due Process Hearings. (December 2019) - Greene, Gary; Landmark, Leena Jo
School compliance with the Individuals with Disabilities Education Act (IDEA) transition services language requirements in this country has been an issue of concern to parents of students with disabilities as well as special education attorneys and advocates for quite some time. Evidence exists in special education case law about court rulings regarding poor transition programming and services provided by school districts to students with disabilities. The purpose of this article is to review literature on these legal cases, describe a small-scale study that investigated the most common transition-related issues mediated by special education attorneys in the state of California, and make recommendations to public school districts on how to avoid transition-related legal disputes on the IDEA transition services language requirements.